Periodontitis correlated with increased ESR and platelet counts in Indonesians with type 2 diabetes mellitus - Hendri Susanto; Frank Abbas (DiscoverSys Inc., 2022)
Background : Periodontitis increases systemic inflammation in type 2 diabetes mellitus (DM2). Platelet count may be increased in periodontitis. The increased systemic inflammation and platelet counts are considered risk factors for atherosclerosis. However, there was no study investigating the correlation between periodontitis and platelet counts in type 2 diabetes mellitus in Indonesians. Objective: To assess the correlation between periodontitis, systemic inflammatory markers and platelet counts in Indonesian DM2 patients. Methods: A full mouth periodontal examination including bleeding on probing, probing pocket depth, gingival recession, and plaque scores was performed in Indonesians DM2 in Dr. Sardjito Hospital, Yogyakarta. Indonesia. In addition, glycated hemoglobin (HbA1c), erythrocyte sedimentation rates (ESR), High sensitivity C reactive protein (Hs-CRP), peripheral blood counts, were assessed. To assess age, body mass index (BMI) education level, ethnicity, sex/gender, smoking, a standardized questionnaire was used and presented descriptively. In correlation and multiple linear regression analyses, it was assessed whether periodontitis operationalized with periodontal inflamed surface area (PISA) correlated with systemic inflammatory markers (Hs-CRP, ESR), HbA1c and peripheral blood counts (hemoglobin, leucocytes, erythrocytes, platelets, hematocrite) with 95% Confidence Interval.Results: In 44 Indonesians treated for DM2, PISA was associated with ESR (r = 0.32; p<0.05), and platelet count (r = 0.527; p < 0.05). Plaque score and PISA were the predictors for platelet count (p<0.05)Conclusion: Periodontitis Is associated with increased the systemic inflammation marker Erythrocyte Sedimentation Rate (ESR) and platelet counts in Indonesians DM2 and therefore may form an additional risk factor for atherosclerosis in these patients.